New factors inducing changes in the retail banking customer relationship management (CRM) and their exploration by the FinTech industry - Marcin Kotarba (Foundations of Management, 2016)
Growing levels of regulation force financial institutions to change their business models toward lower risk levels, higher capital adequacy, service quality, and more stable revenue pools. In parallel with the regulatory changes, the banks are subject to pressure from accelerated technology development and social changes. These two factors influence the behavior of customers and induce changes in the customer relationship management (CRM). Taking the example of retail banking, the factors and their impacts are explained. Additionally, a view on the FinTech industry is presented, highlighting areas where traditional financial institutions are losing market share to technology-savvy and socially oriented new ventures with exceptional CRM capabilities. The conclusion contains proposed strategic actions that need to be undertaken in order to prepare the financial services industry for managing customer relationships in the increasingly technosocial environment.
Keywords: 650; customer relationship management; omni-channel; financial institution strategy; FinTech; banking regulation; retail banking; client behavior; technological progress; process management; customer journey; social empowerment